Optimalisasi Prestasi Belajar Materi Elektromagnet dengan Menggunakan Pendekatan Eksperimen dalam Pembelajaran IPA pada Peserta Didik Kelas IX A SMP Negeri 3 Teras Semester Gasal Kabupaten Boyolali Tahun Pelajaran 2011/2012 - Budiharjo, Budiharjo (Universitas Muhammadiyah Surakarta, 2013)
This research purpose is to describe about effort to increase learning achievement giving task autonomous structure in learning electromagnet material of the studentâs class IX A SMP Negeri 3 Teras Boyolali regency semester 2011/2012. Subject and data source of the research the students class IX A sum 40 students. Collecting data method uses observation, documentation and test. Analysis data uses critic and comparative. Reaching indicator uses KKM 63 and complete target 100%. Research procedure uses cycles. According to achievement of the research and review conclusion if observation result of the teacher in learning from they teach material in the class that gets pre cycle to cycle II shows pre cycle is 50%, cycle I is 74,43% and cycle II is 97,15%. From data shows advance from pre cycle to cycle I is 12,86%, so cycle I to cycle II increases 25,72% and pre cycle to cycle II is 38,58%. Hence, result observation of the teacher in learning shows advance significant. Result observation of the teacher prepares class to learning, data get pre cycle to cycle II, it get advance at pre cycle is 56%, cycle I is 80% and cycle II is 94%. From this data shows advance from pre cycle to cycle I is 24%, so cycle I to cycle II advance 14% and pre cycle to cycle II is 38%. Hence, result observation of the teacher prepares class to learning shows significant. Percentage optimum motivation pre cycle step gets 45%, cycle I is 85% and cycle II is 100%. Hence, it increases from pre cycle to cycle I is 40%, cycle I to cycle II increases 15% and pre cycle to cycle II increases 55%. Hence, motivation of the student in physics learning from pre cycle to cycle II is significant. Percentage learning complete from pre cycle gets 62,5% and cycle I is 67,5% and cycle II is 100%. Pre cycle step to cycle I increases 15% from cycle I to cycle II is 22,5% and Pre cycle to cycle II increases 37,5%. Hence, physics learning achievement of the student from pre cycle to cycle II are significant.